53.8k views
1 vote
Some one help ASAP it’s already 2am I want sleep please help I give crowns

Some one help ASAP it’s already 2am I want sleep please help I give crowns-example-1
User Nelion
by
4.3k points

1 Answer

2 votes

Final Answer:
x = 12

Steps/Reasons/Explanation:

Question: What is the solution to the equation
(1)/(2)x + 3 = (2)/(3)x + 1?

Step 1: Simplify
(1)/(2)x to
(x)/(2).


(x)/(2) + 3 = (2)/(3)x + 1

Step 2: Simplify
(2)/(3)x to
(2x)/(3).


(x)/(2) + 3 = (2x)/(3) + 1

Step 3: Multiply both sides by
6 (LCM of
2, 3).


3x + 18 = 4x + 6

Step 4: Subtract
3x from both sides.


18 = 4x + 6 - 3x

Step 5: Simplify
4x + 6 - 3x to
x + 6.


18 = x + 6

Step 6: Subtract
6 from both sides.


18 - 6 = x

Step 7: Simplify
18 - 6 to
12.


12 = x

Step 8: Switch sides.


x = 12

~I hope I helped you :)~

User Dziraf
by
4.5k points